Correlations of IL-1β and vitamin D with CAT score in patients with acute exacerbation of chronic obstructive pulmonary disease: Correlations of IL-1β and VitD with CAT score in patients with AECOPD - Wang, Lidong; Wang, Mai; Qian, Dan; Ding, Xing; Jiang, Heping (Cellular and Molecular Biology, 2023)
This study was to analyze the correlations of IL-1β and vitamin D (VitD) with chronic obstructive pulmonary disease assessment test (CAT) score in patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). For this purpose, a total of 65 patients with chronic obstructive pulmonary disease (COPD) treated in our hospital between June 2020 and June 2022 were enrolled and assigned to a research group, and 40 healthy individuals who underwent physical examination in our hospital over the same time spanning were enrolled into the control group. The 65 COPD patients were further grouped into a stability group (30 cases) and an exacerbation group (35 cases). The two groups were compared in the levels of 25-hydroxyvitamin D (25(OH)D), interleukin-1β (IL-1β) and blood gas indexes (arterial carbon dioxide partial pressure (PaCO2) and arterial partial pressure of oxygen (PaO2). The modified Medical Research Council Dyspnea Scale (mMRC) and the CAT were adopted for evaluation of the stability group and exacerbation group. The correlations of IL-1β and 25(OH)D with mMRC and CAT scores were analyzed. The diagnostic value of IL-1β and VitD in patients in different stages was analyzed through receiver operating characteristic (ROC) curves. Results showed that the control group showed greatly lower IL-1β and PaCO2 levels and higher 25(OH)D and PaO2 levels than the research group (all P<0.05). The stability group got greatly lower mMRC and CAT scores than the exacerbation group (both P<0.05). IL-1β had positive correlations with mMRC and CAT scores, while 25(OH)D had negative correlations with them (P<0.05). According to ROC curve-based analysis, IL-1β and 25(OH)D had areas under the curves of 0.814 and 0.583, respectively, in diagnosing the acute exacerbation period, and had specificities of 56.67% and 43.33%, respectively and sensitivities of 97.14% and 74.29%, respectively. In conclusion, patients with COPD have increased IL-1 β and VitD deficiency, so VitD can be properly supplemented during treatment, and the levels of inflammatory factors should be paid close attention to at all times. IL-1 β and VitD can be regarded as novel ideas for the diagnosis and treatment of COPD, which may further improve the effect of COPD prevention and treatment.